Improvement in Violacein Production by Utilizing Formic Acid to Induce Quorum Sensing in Chromobacterium violaceum - Kuan-Chen Cheng; Hsiang-Chun Hsiao; Yu-Chen Hou; Chang-Wei Hsieh; Hsien-Yi Hsu; Hung-Yueh Chen; Shin-Ping Lin (MDPI AG, 2022)
Violacein has attracted increasing attention due to its various biological activities, such as antibacterial, antifungal, antioxidative, and antitumor effects. To improve violacein production, formic acid (FA) was added to a culture medium, which resulted in a 20% increase (1.02 g/L) compared to the no-FA-addition group (0.85 g/L). The use of a stirred-tank bioreactor system also improved violacein production (by 0.56 g/L). A quorum-sensing (QS)-related gene (cviI) was induced by FA treatment, which revealed that the mechanism induced by FA utilized regulation of the cviI gene to induce the vio gene cluster for violacein production. To analyze the antioxidative properties of the violacein produced, 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) scavenging tests were conducted, and results reveal that the values of the 50% inhibitory concentration (IC50) of DPPH and ABTS were 0.286 and 0.182 g/L, respectively. Violacein also showed strong inhibitory activity against Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis). In summary, this study found that the addition of formic acid can promote QS of Chromobacterium violaceum, thereby promoting the synthesis of violacein. Subsequently, the promoting effect was also evaluated in a bioreactor system. These findings will be helpful in establishing an economically beneficial production model for violacein in future work.